STUDENT’S ATTITUDE TOWARD LBL VERSUS PBL IN PHARMACOLOGY AT NGMC, BANKE, NEPAL - Dhami, DB; Rathore, RS; Bhargava, VK; Neupane, G; Singh, R.; Singh, A.; Shah, GJ (International Journal of Research -GRANTHAALAYAH, 2017)
Background: Reviewing the teaching program at regular intervals and modifications in the teaching methodologies with understanding perceptions and opinions of medical students regarding teaching learning may prove useful in improving the teaching of pharmacology. The objective of the current study was to compare the effectiveness and to assess perception of Problem based learning (PB) and lecturer based learning (LB) in conveying the medical facts in pharmacology. Methods: A questionnaire was distributed to the students and asked to score each individual statement regarding LBL and PBL. The median total scores and median with interquartile range of individual statements was calculated. A comparison between questions that support LBL or PBL was performed. Student t-test was employed to compare the mean scores of different groups. Result: Among of one hundred and thirty five (135) students, only one hundred and ten (110) student participated in this study. The individual median score was 37 when compared to possible total score of 55. The total score (mean ± standard deviation for question 4-7 related to LBL was 2.920±0.614 and that of the questions 8-11 related to PBL was 3.863 ±0.738. This difference found statistically significant (p<0.05) Conclusion: Students had more positive perception on PBL compared to the LBL. In PBL, Student analyses the problem through self-directed efforts, solves the given problem by applying knowledge and skills followed by group discussions in adequate infrastructure, trained faculty, well-equipped library and internet facility which is always superior to didactic lectures.